Physical activity during the Coronavirus (COVID-19) pandemic: Prevention of a decline in metabolic and immunological functions - Jakobsson, J.; Malm, C.; Furberg, M.; Ekelund, U.; Svensson, M. (Frontiers in Sports and Active Living, 2020)
As of 30th January 2020, the outbreak of the novel coronavirus disease, later called COVID-19, was declared a Public Health Emergency (World Health Organization, 2020b) and on the 11th of March 2020, COVID-19 was characterized as a pandemic (World Health Organization, 2020d). On April 20th 2020, WHO reported 2,314,621 confirmed cases of COVID-19 and a total of 157,847 deaths from all regions of the world (World Health Organization, 2020a).